Effect modification of FADS2 polymorphisms on the association between breastfeeding and intelligence: protocol for a collaborative meta-analysis. Issue 6 (15th June 2016) - Hartwig, Fernando Pires; Davies, Neil Martin; Horta, Bernardo Lessa; Victora, Cesar Gomes; Davey Smith, George
Abstract : Introduction: Evidence from observational studies and randomised controlled trials suggests that breastfeeding is positively associated with IQ, possibly because breast milk is a source of long-chain polyunsaturated fatty acids. Different studies have detected gene-breastfeeding interactions involving FADS2 variants and intelligence. However, findings are inconsistent regarding the direction of such effect modification. Methods/design: To clarify how FADS2 and breastfeeding interact in their association with IQ, we are conducting a consortium-based meta-analysis of independent studies. Results produced by each individual study using standardised analysis scripts and harmonised data will be used. Inclusion criteria : breastfeeding, IQ and either rs174575 or rs1535 polymorphisms available; and being of European ancestry. Exclusion criteria : twin studies; only poorly imputed genetic data available; or unavailability of proper ethics approval. Studies will be invited based on being known to have at least some of the required data, or suggested by participating studies as potentially eligible. This inclusive approach will favour achieving a larger sample size and be less prone to publication bias. Discussion: Improving current understanding of FADS2 -breastfeeding interaction may provide important biological insights regarding the importance of long-chain polyunsaturated fatty acids for the breastfeeding-IQ association. This meta-analysis will help to improve such knowledge by replicating earlier studies, conducting additional analysis and evaluating different sources of heterogeneity. Publishing this protocol will minimise the possibility of bias due to post hoc changes to the analysis protocol.